2015
DOI: 10.5152/iao.2015.642
|View full text |Cite
|
Sign up to set email alerts
|

Role of Laryngopharyngeal Reflux in the Pathogenesis of Otitis Media with Effusion

Abstract: OBJECTIVE:To determine whether there is an association between otitis media with effusion and laryngopharyngeal reflux in children. MATERIALS and METHODS:This study included 31 children with otitis media with effusion. The pepsinogen level in the middle ear fluid of all patients was measured by sandwich enzyme-linked immunosorbent assay. Each patient's middle ear fluid was investigated for Helicobacter pylori (H. pylori) using the Campylobacter-like organism (CLO) test. The middle ear pepsinogen levels were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 22 publications
0
33
0
1
Order By: Relevance
“…The link between GOR and OME has been suspected ever since pepsins and Helicobacter pylori were found in samples of middle ear effusion (Formanek et al., 2015; Dogru et al., 2015). However, a direct causal relationship between GOR and OME has not been demonstrated (Miura et al., 2012; Morinaka et al., 2005).…”
Section: The Physiopathology Of Omementioning
confidence: 99%
“…The link between GOR and OME has been suspected ever since pepsins and Helicobacter pylori were found in samples of middle ear effusion (Formanek et al., 2015; Dogru et al., 2015). However, a direct causal relationship between GOR and OME has not been demonstrated (Miura et al., 2012; Morinaka et al., 2005).…”
Section: The Physiopathology Of Omementioning
confidence: 99%
“…The current survey reveals similar lack of awareness of the potential role of LPR in development of laryngotracheal stenosis and chronic media otitis, despite an increasing literature which supports this relationship. 10,11,26,27 Surprisingly, non-laryngologists seem to be unaware about the role of LPR in bronchial diseases such as asthma; however, many studies have demonstrated that LPR is involved in the development of bronchial hypersensitivity conditions, such as asthma, 28,29 or chronic obstructive pulmonary disease. 30 In the current survey, the largest differences between laryngologists and non-laryngologists concern diagnostic approach towards LPR, particularly with regard to examinations such as esophagoscopy and MII-pH.…”
Section: Discussionmentioning
confidence: 99%
“…the eustachian tube may be attributed to mucosal inflammation, toxicity, and osmosis of bile acid in an acidic environment after LPRD [17]. LPRD is associated with the occurrence and progress of secretory otitis media [18], and it can make secretory otitis media progress more rapidly [19]. Obesity is one of the influencing factors of LPRD, and patients with an abnormal BMI often have a high risk of LPRD [20].…”
Section: Discussionmentioning
confidence: 99%